Convenient Synthesis of Ellagic Acid from Methyl Gallate and SARS-CoV-2 3CLpro Antiviral Activity - Navarro, Francesc; Hamri, Salha; Reches, Rosa; Viñas, Miquel; Jahani, Daniel; Ginard, Jaume; Vilardell, Josep; Abián, Olga; Pujol, M. Dolors (Synthesis, 2022)
A practical synthesis of ellagic acid has been achieved from methyl gallate by a proposed synthetic route of five steps, consisting of ketal protection, regioselective bromination, bis-lactonization, C–C bond formation between the aromatic rings of the galloyl groups, and ketal deprotection, in 38% overall yield. Ellagic acid showed a slight inhibitory activity against SARS-CoV-2 3CLpro.
Keywords: ellagic acid; gallic acid; polyphenols; reductive coupling; ketals